A trade policy framework for the European Union-United Kingdom reset - Ignacio García Bercero (Bruegel, 2024)
A reset in the relationship between the United Kingdom and the European Union is underway, with agreement that leaders will meet in an EU-UK Summit in the first half of 2025. By that time it can be expected that there would be greater clarity about what the reset could imply for trade between the EU and the UK, which is governed currently by the EU-UK Trade and Cooperation Agreement (TCA). There is a common interest in improving trade relations between the EU and the UK, which remains the EU's second largest trading partner. This Policy Brief recommends that the main elements of the reset in terms of trade should be: Reinforced cooperation on global trade and economic challenges through a new ministerial forum; The negotiation of three legally binding agreements that would complement the TCA: a veterinary agreement, an agreement to link emissions trading system, and an agreement on youth mobility and cultural facilitation; A new framework to reinforce regulatory cooperation. These recommendations aim primarily to introduce a new dynamic into the EU-UK trade relationship, focused on the achievement of mutual gains. The economic impact of the suggested legally binding agreements might be limited, but they would help to rebuild mutual trust and deliver some meaningful trade-facilitation steps and, ultimately, further trade-facilitating agreements. The reinforced regulatory cooperation framework, though not legally binding, could potentially have a greater economic impact if it leads to a genuine effort to maintain compatibility of regulatory regimes.
Keywords: 330